Humidity Sensor Based on rGO-SDS Composite Film - Cheng Lei; Junna Zhang; Ting Liang; Ruifang Liu; Zhujie Zhao; Jijun Xiong; Kai Yin (Micromachines, 2022)
Based on the humidity testing requirements in different environments, this paper investigates the humidity sensitivity of reduced graphene oxide (rGO)-sodium dodecyl sulfate (SDS) composite film humidity sensor. In the experiments, rGO-SDS dispersions with a concentration of 5 mg/mL were prepared, and a microelectromechanical system (MEMS) process was used to prepare the interdigital electrodes. The dispersions were then drop-coated on the interdigital electrodes and dried on a heated plate at 100 °C. The surface characteristics of the rGO-SDS films transferred onto SiO2-Si substrates were analyzed by scanning electron microscopy, raman spectroscopy and atomic force microscopy, infrared spectroscopy, X-ray photoelectron spectroscopy, and tested by a correlation system, which showed a linear relationship between humidity variation and the resistance variation of the sensor in the ambient humidity range of 25–95% RH. At room temperature, the linearity of the sensor is about 0.98431 and the sensitivity is about 11.41432 Ω/% RH. At 100 °C, the correlation of the sensor is about 0.95046 and the sensitivity is about 1.0145 Ω/% RH; with a response time of only 9 s at ambient humidity from 25% RH to 95% RH, the sensor has very good repeatability and stability.